Single session of pattern scanning laser versus multiple sessions of conventional laser for panretinal photocoagulation in diabetic retinopathy: Efficacy, safety and painfulness - Nemcansky, Jan; Stepanov, Alexandr; Nemcanska, Sabina; Masek, Petr; Langrova, Hana; Studnicka, Jan (PloS one, 2019)
PURPOSE: To evaluate the clinical efficiency, safety and painfulness of retinal laser photocoagulation employing a pattern scanning laser system Pascal given in a single-session versus conventional laser multiple-session treatment of the same patient with diabetic retinopathy during 12-month follow-up. METHODS: The cohort included 60 eyes in 30 patients treated at the Ophthalmology Clinic, Faculty Hospital Ostrava, from 2008 to 2013. Panretinal laser coagulation was performed on one eye using the multispot panretinal photocoagulation given in a single-session system Pascal (OptiMedica, Santa Clara, California). On the other eye laser treatment was carried out by the classic conventional multiple-session method. RESULTS: The performance of Pascal panretinal laser coagulation was evaluated as significantly less painful (visual scale of pain was 3.28 ± 1.9) than the performance of conventional photocoagulation (visual scale of pain was 3.93 ± 1.88) with similar efficiency. Distribution of progression of diabetic retinopathy in individual patients was very similar in both groups under comparison, and was strictly paired in 24 of the 30 patients at the end of 1-year follow-up. CONCLUSION: Laser photocoagulation of the retina with the use of short impulse durations and patterns in patients with diabetic retinopathy given in one session possesses similar efficiency to that of conventional retinal photocoagulation in multiple sessions. The single session treatment is also better tolerated by patients and in addition to this, it shortens the performance of the whole therapy, which potentially saves considerable funds of all subjects participating in the process of treatment. TRIAL REGISTRATION: ClinicalTrials.gov NCT03672656.
Keywords: Patient Safety; senioři; Treatment Outcome; Disease Progression; progrese nemoci; bezpečnost pacientů; výsledek terapie; Middle Aged; mužské pohlaví; Pain; Adult; Diabetic Retinopathy; retina; Follow-Up Studies; Pain Measurement; měření bolesti; Laser Coagulation; následné studie; Retina; ženské pohlaví; Humans; Lasers; laserová koagulace; lidé středního věku; dospělí; Female; Aged; bolest; diabetická retinopatie; lasery; lidé; Male